2005
DOI: 10.1038/sj.emboj.7600672
|View full text |Cite
|
Sign up to set email alerts
|

The yeast lipin Smp2 couples phospholipid biosynthesis to nuclear membrane growth

Abstract: Remodelling of the nuclear membrane is essential for the dynamic changes of nuclear architecture at different stages of the cell cycle and during cell differentiation. The molecular mechanism underlying the regulation of nuclear membrane biogenesis is not known. Here we show that Smp2, the yeast homologue of mammalian lipin, is a key regulator of nuclear membrane growth during the cell cycle. Smp2 is phosphorylated by Cdc28/ Cdk1 and dephosphorylated by a nuclear/endoplasmic reticulum (ER) membrane-localized C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
736
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(763 citation statements)
references
References 53 publications
26
736
1
Order By: Relevance
“…4) are phosphorylated in several (Ser/Thr)-Pro phosphorylation sites, it is interesting to speculate that one or more of the protein kinases and/or phosphatases acting on lipin proteins in yeasts and mammals have been conserved. Santos-Rosa et al (10) have presented evidence that the yeast Pah1p is dephosphorylated by a membrane-localized CPD phosphatase complex, Nem1/Spo7. Thus, it is interesting to speculate that Dullard (35), the mammalian homolog of yeast Nem1, might be a lipin phosphatase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) are phosphorylated in several (Ser/Thr)-Pro phosphorylation sites, it is interesting to speculate that one or more of the protein kinases and/or phosphatases acting on lipin proteins in yeasts and mammals have been conserved. Santos-Rosa et al (10) have presented evidence that the yeast Pah1p is dephosphorylated by a membrane-localized CPD phosphatase complex, Nem1/Spo7. Thus, it is interesting to speculate that Dullard (35), the mammalian homolog of yeast Nem1, might be a lipin phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is interesting to speculate that Dullard (35), the mammalian homolog of yeast Nem1, might be a lipin phosphatase. Yeast Pah1p is believed to be phosphorylated by the cyclin-dependent kinases Cdc28p and/or Pho85p (10,34). Although there may be instances in which mammalian homologs of Cdc28, such as Cdc2, Cdk2, and Cdk3, phosphorylate lipin, the activities of most cyclin-dependent kinases are relatively low in terminally differentiated adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of Spo7p, an inhibitor of phospholipid biosynthesis, leads to the appearance of a single "flare"like nuclear protrusion that can be seen using a soluble nuclear protein, such as Pus1p, fused to GFP (Siniossoglou et al, 1998;Santos-Rosa et al, 2005; Figure 1A). The most parsimonious explanation for this phenotype is that the increase in phospholipid biosynthesis leads to nuclear membrane expansion (Santos-Rosa et al, 2005).…”
Section: Characterization Of the Spo7⌬ Nuclear "Flares"mentioning
confidence: 99%
“…Our analysis of the spo7⌬ mutant phenotype suggests that the nuclear membrane associated with the nucleolus has certain properties that distinguish it from the membrane surrounding the rest of the nucleus, because in the absence of Spo7p function only the nucleolus-associated membrane becomes extended (Figure 4). The involvement of Spo7p in inhibiting phospholipid biosynthesis (Santos-Rosa et al, 2005) strongly suggests that the flare is a result of membrane proliferation due to elevated levels of phospholipids, rather than an expansion of the nucleolus itself. Indeed, we found that when the nucleolus was no longer intimately associated with the nuclear envelope, such as in a strain in which the only rDNA copies were on plasmids and expressed by Pol II (Oakes et Figure 6.…”
mentioning
confidence: 99%
See 1 more Smart Citation